PRODUCTIVITY OF COTTON LINES IN VARIOUS SOIL AND CLIMATIC CONDITIONS OF UZBEKISTAN - Juraev S. T.; Mo Hwang Sung; Xolikova K. (Modern American Journals, 2025)
The productivity of cotton lines of the G.hirsutum L. species was estimated in the Tashkent, Fergana and Kashkadarya regions of the Republic of Uzbekistan. Ten lines of different genetic origin were tested. The influence of genotype and environment on their productivity was analyzed. The results of three-year experiments showed that the environment has a greater effect on the variability of a trait than the genotype. To find the optimal variety-geographical point option, it is necessary to conduct a series of tests.
Keywords: Yield, cotton (Gossypium hirsutum L.), genotype, environment, analysis of variance, genotype–environment interaction, regional trials, trait stability.